The efficacy of inferior vena cava diameter, perfusion index and pleth variability index on predicting hypotension in spinal anesthesia (Annals of Medical Research, 2022)
Aim: One of the most common side effects of spinal anesthesia (SA) is hypotension. The aim of the study was to evaluate the efficacay of inferior vena cava (IVC) diameter measurements, perfusion index (PI) and pleth variability index (PVI) values in determining the risk of developing hypotension after SA.Materials and Methods: This study was conducted on 81 patients who underwent transurethral prostatectomy.  Before administration of SA, PI and PVI values, IVC diameters (IVCmin: during inspiration and IVCmax: during expiration) and IVC collapsibility index (IVCCI) values and non-invasive blood pressure were recorded. Patients with a baseline systolic arterial pressure reduction rate of ≥25% were determined as the group developing hypotension. IVC diameter measurements were measured immediately after SA then 5 min, and at the end of the operation. The heart rate, mean arterial pressure, PI and PVI values were recorded at regular intervals.Results: Hypotension occured in 32 patients (39.5%). In the hypotensive group, IVCmax and IVCmin values were observed lower and IVCCI values higher. The optimal threshold value of IVCmin was ≤0.99 and threshold value of IVCCI was >%44.5 for predicting hypotension after SA.Conclusion: While IVCmin and IVCCI values were effective in determining hypotension risk after SA, PI and PVI values were not. To predict hypotension by IVC diameter measurements after SA will allow a more effective intervention and avoid hypotension.